Prototypical supervisors shape lay‐off victims' experiences of top management justice and organizational support. Issue 1 (20th December 2017) - Lipponen, Jukka; Steffens, Niklas K.; Holtz, Brian C.
Abstract : Job loss is a pervasive experience affecting millions of workers around the globe annually. To investigate lay‐offs from the perspective of those who are affected, we conducted a lagged study examining lay‐off victims' experiences of supervisory justice, top management justice, and organizational support. We test the hypotheses that the relationships between supervisory justice and lay‐off victims' subsequent experiences of top management justice as well as organizational support are moderated by supervisors' prototypicality of their team. Results from our study conducted during lay‐off process indicated that supervisory justice had a positive lagged impact on lay‐off victims' unfolding experiences of both (1) top management justice and (2) organizational support for supervisors who were viewed as highly (but not lowly) prototypical of the team that both supervisors and subordinates were part of. Our study identifies a theoretically grounded moderator that may account for the presence (or absence) of cross‐foci effects found in previous multifoci justice studies. Moreover, our results shed light on the development of justice perceptions by demonstrating the impact of lower‐level supervisors in translating subordinates' perceptions of justice of the supervisor to that of the top management. Findings suggest that supervisors have an important role to play in managing (for better or worse) the potentially harmful consequences associated with organizational redundancies. Practitioner points: Prototypical supervisors are 'gatekeepers' who are able to influence their subordinates' relationship with the organization and its management. Involving supervisors in critical events such as lay‐offs may be important to effectively manage employees' concerns. It may not be well advised to overly centralize responsibility for communicating information regarding lay‐offs under human resource departments.